Climatic impact on urban heritage building : case study on a British colonial residence : JKR 989 in Kuala Lumpur / Tiew Si Yee - Tiew, Si Yee (2012)
Malaysia is a hot and humid tropical country that has yearly mean temperature between 24°C and 33°C and relative humidity between 70% and 90% throughout the year. Thus, overheating is a paramount problem in residential buildings. Although air conditioning can solve this problem, it will consume a large amount of electricity and also causes environmental problems. Moreover, the concern of sick building syndrome has resulted in a resurgence of interest in naturally ventilated rooms. The action of opening a window is the most intuitive and simple response to controlling overheating in a room. Even so, if the window opening dimension is not properly designed, direct sunlight through the window will contribute by far the largest heat gain in houses. The survival of vernacular houses especially in the tropics should be reviewed to identify window design strategies that had been applied for natural ventilation and daylight. This study provides an evaluation on the window design performance in urban area and evaluation of impact of microclimate on indoor thermal comfort of the inhabitants based on case study on a selected British Colonial residences in Kuala Lumpur, Malaysia. The result suggests optimum window design for similar residences in urban area. The evaluation was conducted based on the calculation of window to wall ratio, field measurement, and simulation test using AIOLOS. Architecture and window design approaches of the selected residences were analyzed and the data collected from each residence were applied in the calculation of window to wall ratio. The validations of the window to wall ratio were then examined by field measurement and simulation using AIOLOS software. The research reveals that the thermal condition of the selected residence was higher than Malaysia standard requirements. In addition, existing surrounding buildings imposed a deep impact on the microclimate of JKR 989 which directly influenced the windows performance of the building.